Meningkatkan Keterampilan Membaca Permulaan dengan Metode Struktural Analitik Sintetik (SAS) pada Mata Pelajaran Bahasa Indonesia Kelas II SDN 1 Teluk Betung Tahun Pelajaran 2022 - Saputra, Hendra; Astari, Maya (STKIP PGRI Bandar Lampung, 2022)
This study aims to: (1) improve the initial reading skills of second grade students of SD Negeri 1 Teluk Betung (2) to observe the activities of students in early reading skills using the Structural Analytic Synthetic (SAS) method. This type of research is classroom action research with the design used is the Kemmis and Mc Taggart model. This classroom action research uses 2 cycles where each cycle is carried out according to the research model, namely planning, implementation or action, observation, and reflection. The research subjects consisted of 26 students of which 15 were male students and 11 were female students. The method used is the Structural Analytical Synthetic (SAS) method with data collection using: observation sheets, reading ability tests, and documentation. The results of the research on early reading skills using the Structural Analytic Synthetic (SAS) method were able to improve early reading skills. It is proven by the existing data that at the initial condition, namely 46.15% of students who meet the criteria for completeness, then there is an increase when using word card media in the first cycle with an average of 72.84 or 57.69% of students who meet the criteria. the value of completeness criteria, and experienced a good increase when the second cycle was carried out using word card media with various colors with an average of 80.42 or 80.76% of students who met the Minimum Completeness Criteria (KKM).